Indonesia National Curriculum Reform in the Context of Standard-Based Education: Policy and Implementation - Suryadi, Bambang; Rahmawati, Yuli; Hayat, Bahrul; Suprananto, Suprananto (TARBIYA: Journal of Education in Muslim Society, 2019)
AbstractCurriculum reform plays an essential role in assuring the success of systematic educational change. The purpose of this study is to portray the government policy and the issues of the Curriculum 2013 implementation. This study employed qualitative methodology using document analysis, observation and Focused Group Discussion (FGD)   as data collection techniques. The results of this study show that the curricula philosophy of curriculum reform was well-articulated and relevant to meet the requirements of twenty-first century learning competencies. However, the curricula implementation process faced substantial challenges with technical problems regarding the national standards of education document, teacher training and competences, the availability of school textbooks, and classroom assessment implementation. The findings of this study have several implications for implementing the national curriculum in Indonesia. Therefore, alignment between the national standards of education document, the curriculum structure, and the assessment system is required in order to ensure the successful implementation of Curriculum 2013 throughout the nation.AbstrakReformasi kurikulum memainkan peran penting dalam memastikan keberhasilan perubahan pendidikan yang sistematis. Tujuan dari penelitian ini adalah untuk menggambarkan kebijakan pemerintah dan isu-isu implementasi Kurikulum 2013. Penelitian ini menggunakan metodologi kualitatif menggunakan analisis dokumen, observasi dan diskusi kelompok terpumpun sebagai teknik pengumpulan data. Hasil penelitian ini menunjukkan bahwa filosofi reformasi kurikulum diartikulasikan dengan baik dan relevan untuk memenuhi persyaratan kompetensi pembelajaran abad kedua puluh satu. Namun, proses implementasi kurikulum menghadapi tantangan besar dengan masalah teknis mengenai dokumen yang terkait dengan standar nasional pendidikan, pelatihan dan kompetensi guru, ketersediaan buku pelajaran di sekolah, dan implementasi penilaian di dalam kelas. Temuan penelitian ini memiliki beberapa implikasi untuk menerapkan kurikulum nasional di Indonesia. Oleh karena itu, diperlukan keselarasan antara dokumen standar nasional pendidikan, struktur kurikulum, dan sistem penilaian untuk memastikan keberhasilan implementasi Kurikulum 2013 di seluruh negara.